The Erythrocyte Sedimentation Rate (ESR) in Veterinary Medicine: A Focused Review in Dogs and Cats - Daniela Diamanti; Carolina Pieroni; Maria Grazia Pennisi; Veronica Marchetti; Eleonora Gori; Saverio Paltrinieri; George Lubas (Animals)
The erythrocyte sedimentation rate (ESR) measures the rate at which erythrocytes aggregate and sediment in a fixed time in an anticoagulated blood tube and is expressed as a speed (mm/h). The ESR is still widely used in human medicine mainly as a modified or alternate method to the original Westergren. In veterinary medicine, it was employed in the 1940s–1960s after which it was gradually abandoned or rarely employed. More papers using the Westergren method have been published in dogs rather than in cats. In recent years, the test has regained importance. This narrative review describes the principle of ESR, which is related to the increase in a few acute response proteins such as fibrinogen, immunoglobulin M, and α2-macroglobulin which act to aggregate RBCs. Reference intervals were established for dogs and cats for the original and modified Westergren method. The ESR is mainly used to detect inflammatory conditions derived from infection, urinary or orthopedic disorders, and also miscellaneous diseases. The application of the modified ESR is supported by appropriate reference intervals; however, further studies are needed to assess the influence of age, sex, and breed both for dogs and cats.